ORGANIZATIONAL PRINCIPLES OF MEDICAL AID TO GUNSHOT WOUNDS OF THE ABDOMEN AT THE FRONT STAGES - Shapovalov, V.Yu.; Herasymenko, O.S.; Khoroshun, E.M.; Yenin, R.V.; Shepitko, K.V.; Herasymenko, S.D. (World of Medicine and Biology, 2019)
The analysis on the results of treatment in 496 wounded with abdominal warfare injuries undergoing treatment in military mobile hospitals from June 2014 was carried out by August 2017. 3 groups of comparison were identified: group 1 - injured, treated during the period from June 12, 2014 to August 31, 2015 (control group); group 2 - injured persons who were treated between September 1, 2015 and August 31, 2016 (experimental group 1); group 3 - injured persons who were treated between September 1, 2016 and August 31, 2017 (experimental group 2). Group 1 included 161 wounded middle-aged 32.3 ± 2.5 years; group 2 - 177 wounded by middle age 34,1 ± 2,3 years; group 3 - 158 wounded with an average age of 33.2 ± 2.4 years. All wounded were men. The purpose of the work was to improve the treatment results in wounded with abdominal injuries based on optimization of the treatment and evacuation process in the conditions of combat operations. The relationship between the results of treatment of wounded people in the abdomen with the onset and quality of surgical care, with the terms and type of medical evacuation from different levels of medical care, creates great organizational difficulties, especially with the mass influx of wounded. The purpose of the work was improving the results of treatment of the wounded with combat damage to the abdomen on the basis of optimization of the medical-evacuation process in combat conditions. The results of treatment of 496 wounded with combat abdominal injuries treated in military mobile hospitals from June 2014 to August 2017 were analyzed. The widespread use of armored ambulance transport when evacuating from the front edge is essential for the safe transportation of the wounded to level I medical care. For transportation of wounded from I to II level of medical care, it is advisable to use reanimation mobiles with simultaneous anti-shock measures in the amount of first aid. The use of sequential labeling of wounded arriving at levels II-IV of medical care, in addition to “traditional” triage, can significantly shorten the time between admission and the start of medical care for massive single-step proceeds. Evacuation of the wounded with a dominant head injury (or with damage to the organ of vision) from the helicopter landing sites close to the contact line (bypassing level II) helps save time and speed up delivery to a specialized hospital. The study performed permits to make the following conclusions: 1. In the context of modern combat operations, the use of armored sanitary transport is necessary for the evacuation of the wounded from the front. 2. During transportation of the wounded with І and ІІ level of medical care it is expedient to use class B reanimobiles with the simultaneous taking of antishock measures. 3. The sequential marking of the wounded can significantly reduce the period between the arrival and the beginning of medical care in case of massive simultaneous hospitalization. 4. Evacuation of wounded with dominant cranial injuries (or injuries to the organ of vision) from close to the front line airfield heliport (passing level II) contributes to saving time and faster delivery to a specialized hospital.